Biomechanical evaluation of a novel repair strategy for intervertebral disc herniation in an ovine lumbar spine model - Page, Mitchell I.; Easley, Jeremiah T.; Bonilla, Andres F.; Patel, Vikas V.; Puttlitz, Christian M. (Frontiers in Bioengineering and Biotechnology, 2022)
Following herniation of the intervertebral disc, there is a need for advanced surgical strategies to protect the diseased tissue from further herniation and to minimize further degeneration. Accordingly, a novel tissue engineered implant for annulus fibrosus (AF) repair was fabricated via three-dimensional fiber deposition and evaluated in a large animal model. Specifically, lumbar spine kinetics were assessed for eight (n=8) cadaveric ovine lumbar spines in three pure moment loading settings (flexion-extension, lateral bending, and axial rotation) and three clinical conditions (intact, with a defect in the AF, and with the defect treated using the AF repair implant). In ex vivo testing, seven of the fifteen evaluated biomechanical measures were significantly altered by the defect. In each of these cases, the treated spine more closely approximated the intact biomechanics and four of these cases were also significantly different to the defect. The same spinal kinetics were also assessed in a preliminary in vivo study of three (n=3) ovine lumbar spines twelve weeks post-implantation. Similar to the ex vivo results, functional efficacy of the treatment was demonstrated as compared to the defect model at twelve weeks post-implantation. These promising results motivate a future large animal study cohort which will establish statistical power of these results further elucidate the observed outcomes, and provide a platform for clinical translation of this novel AF repair patch strategy. Ultimately, the developed approach to AF repair holds the potential to maintain the long-term biomechanical function of the spine and prevent symptomatic re-herniation.